Conform or challenge? Adjustment strategies of sanction‐torn companies. (27th July 2020) - Weber, Patrick Maximilian; Stępień, Beata
Abstract: The literature on sanctions often neglects the role of domestic firms in sender states, although sanctions only have a real economic effect when senders' firms reduce their activities on the target's market. In contrast, sanctions avoidance and increasing investments in the target country (the observed behaviour of many companies facing the EU sanctions against Russia imposed in 2014) mitigate the impact of these restrictive measures. While sanctions increase the political risk for companies, they also offer economic opportunities—and previous studies could not settle the debate on which factor prevails. By evaluating responses from British, French, German, Italian and Polish enterprises to an online survey distributed in 2017, we analyse at the firm level how sanction‐torn companies adjust to new political orders and what drives their strategic decisions. We find evidence that resource dependency induces strategies that challenge sanction policies: in particular, non‐fungible assets in the target country incentivise companies to further increase their engagement. These defiance strategies diminish the real economic effect of sanctions and generate a new economic equilibrium, which has negative long‐term implications on the choice set of policymakers to further pursue the imposition of sanctions and which even outlasts the lifting of these restrictive measures.